Preparation method of alumina array modified methanol synthesis catalyst

The combination of nanorod-shaped porous alumina array and copper-zinc slurry was prepared by in-situ ammonia distillation method to form a catalyst for alumina array modification, which solved the problem of active particles migration and agglomeration in Cu-ZnO-Al2O3 catalyst, and significantly improved the Thermal stability and service life of the catalyst.

CN119186540APending Publication Date: 2024-12-27CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310741218.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the existing Cu-ZnO-Al2O3 catalyst, the particle size of Cu increases with the increase of reaction time, and Al2O3 exists as an inert framework, which cannot effectively block the migration and agglomeration of active particles, affecting the thermal stability of the catalyst.

Method used

The nanorod-shaped porous alumina array is prepared by in-situ ammonia vaporization method, and mixed it with copper-zinc slurry. Through washing, drying and calcining processes, a catalyst for alumina array modification is formed, which limits the migration path of copper-zinc nanoparticles and enhances the Cu-Zn-Al相互作用,阻断粒子迁移通道。

Benefits of technology

It significantly improves the thermal stability of the catalyst, extends the service life of the catalyst, improves the initial activity and heat resistance activity, and reduces the activity decline rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to an alumina array modified methanol synthesis catalyst and a preparation method thereof, a nanorod-like porous alumina array is obtained by using an in-situ ammonia distillation method, the nanorod-like porous alumina array is uniformly mixed with copper-zinc slurry, and the methanol synthesis catalyst is obtained through washing, drying, roasting and other processes. The nanorod-shaped porous alumina carrier is used for limiting the range of the copper-zinc active particles, so that the heated migration path of the particles is blocked, and the thermal stability of the catalyst is improved. Through the strategy, on one hand, the nanorod-shaped porous aluminum oxide array carrier in the catalyst can limit copper-zinc nanoparticles in regular pore channels of the carrier to form relatively strong Cu-Zn-Al interaction, so that the migration and agglomeration trend of the particles is slowed down; and on the other hand, a particle migration and agglomeration channel can be blocked through the formation of the rod-shaped array. The Al2O3 nanorod array can play a role in blocking an active particle migration channel and preventing active particles from being agglomerated due to heating regardless of a microscopic pore channel or a macroscopic morphology, so that the purpose of improving the thermal stability of the catalyst can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an aluminum oxide array-modified methanol synthesis catalyst, and belongs to the technical field of catalyst preparation. Background Art

[0002] Methanol synthesis catalyst is a key factor in determining the effect of methanol synthesis reaction. At present, the most widely used methanol synthesis catalyst in industry is Cu-ZnO-Al2O3 catalyst, which can well adapt to the current industrial methanol synthesis temperature of 200-280 °C and medium-low pressure reaction conditions of 4-8 MPa ( Chem. Rev. , 2017, 117 , 9804−9838). However, as an active component of the catalyst, Cu has a relatively low surface atomic migration temperature and lattice migration temperature. Specifically, the particle size of Cu in the catalytic reaction will gradually increase with the extension of the reaction time, which will reduce the accessible active sites, resulting in a decrease in catalytic activity and seriously affecting the service life of the catalyst ( Hangzhou Chemical Industry , 2005, 36(1) , 25).

[0003] Introducing Al2O3 components into catalysts can support the active components of catalysts, increase the specific surface area of ​​catalysts, and enhance the stability of catalysts. However, the Al2O3 components introduced into catalysts usually exist in an amorphous form, without obvious crystallinity, specific morphology, and internal pores ( Petrochemical , 2016, 45(1), 24). As a result, Al2O3 exists in the catalyst only as an inert skeleton support, which has a weak interaction with the copper-zinc active particles and cannot block the thermal migration and agglomeration trend of the active particles.

[0004] If a crystalline, porous, fixed-morphology Al2O3 nanorod array is obtained through structural design, the following effects can be achieved: (1) A portion of the copper-zinc nanoparticles are confined in the regular pores of the Al2O3 nanorods, forming a strong Cu-Zn-Al interaction, which slows down the migration and agglomeration trend of the particles; (2) The copper-zinc nanoparticles outside the pores of the Al2O3 nanorods are separated from each other by the Al2O3 nanorod arrays, blocking the particle migration and agglomeration channels. Whether in terms of microscopic pores or macroscopic morphology, the Al2O3 nanorod arrays can block the migration channels of active particles and prevent the active particles from agglomerating under heat, thereby achieving the purpose of improving the thermal stability of the catalyst. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing an alumina array-modified methanol synthesis catalyst, wherein a nanorod-shaped porous alumina array is obtained by an in-situ ammonia evaporation method, the nanorod-shaped porous alumina array is evenly mixed with a copper-zinc slurry, and then a methanol synthesis catalyst is obtained after washing, drying, calcining and other processes, and the copper-zinc active particles are confined by a nanorod-shaped porous alumina carrier to block the thermal migration path of the particles, thereby improving the thermal stability of the catalyst.

[0006] The present invention provides a method for preparing the catalyst, which specifically comprises the following steps: 1. Neutralize copper salt, zinc salt and alkaline precipitant to obtain copper-zinc slurry.

[0007] Preferably, the copper salt and the zinc salt are both soluble nitrates, sulfates and chlorides.

[0008] Preferably, the alkaline precipitant is one of NaOH, NH3·H2O, NaHCO3, and Na2CO3.

[0009] Preferably, the operating conditions for forming the precipitate are: pH 5-9, and precipitation temperature 30-90 °C.

[0010] 2. Neutralize the aluminum salt with ammonia water.

[0011] Preferably, the operating conditions for forming the precipitate are: pH 5-9, and precipitation temperature is room temperature-60 °C.

[0012] 3. After the aluminum slurry is heated, the ammonia is evaporated.

[0013] Preferably, the method for evaporating ammonia is as follows: the temperature is 80-100 °C and the evaporation time is 12-24 h.

[0014] 4. The container is sealed, and the aluminum slurry is heated in situ and reacted again to obtain a nanorod-shaped porous alumina array precursor.

[0015] Preferably, the temperature of the in-situ temperature heating reaction is 180-220 °C, and the reaction time is 24-48 h.

[0016] 5. Mix the nanorod-shaped porous alumina array precursor with copper-zinc slurry, and wash, dry, and calcine the mixture to obtain an alumina array-modified methanol synthesis catalyst.

[0017] Preferably, the molar ratio of copper, zinc and aluminum is 10:5:1-10:5:10.

[0018] Preferably, the drying process is performed at 80-120 °C for 6-12 hours.

[0019] Preferably, the calcination process is performed in an air atmosphere at 300-400 °C for 30-60 minutes.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides a method for preparing an alumina array-modified methanol synthesis catalyst, wherein a nanorod-shaped porous alumina array is obtained by an in-situ ammonia evaporation method, the nanorod-shaped porous alumina array is evenly mixed with a copper-zinc slurry, and then the methanol synthesis catalyst is obtained after washing, drying, calcining and other processes.

[0021] The preparation method of the present invention utilizes a nanorod-shaped porous alumina array carrier to confine copper-zinc nanoparticles in the regular pores of the carrier, forming a strong Cu-Zn-Al interaction and slowing down the tendency of particle migration and agglomeration; on the other hand, the formation of the rod-shaped array can block the particle migration and agglomeration channels. Regardless of the microscopic pores or macroscopic morphology, the Al2O3 nanorod array can block the active particle migration channels and prevent the active particles from agglomerating under heat, thereby achieving the purpose of improving the thermal stability of the catalyst. Implementation

[0022] The following specific examples are only used to further illustrate the technical solutions of the present invention in detail, and the effects of the methods of the present invention are not limited thereto.

[0023] Example 1 241.6 g of copper nitrate trihydrate and 148.7 g of zinc nitrate hexahydrate were dissolved in 1 L of distilled water. The mixed solution and 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 ° C and the pH of the solution in the continuous neutralization reactor was controlled to 5.0.

[0024] 37.5 g of aluminum nitrate nonahydrate was dissolved in 100 mL of distilled water and neutralized with ammonia water at room temperature, with an end point pH of 5.0. After neutralization, the aluminum paste was heated to 80 °C for 12 h in situ to evaporate the ammonia. Subsequently, the slurry after ammonia evaporation was sealed and heated to 180 °C for 24 h to obtain a nanorod-shaped porous alumina array precursor.

[0025] The copper-zinc slurry was mixed with the nanorod-shaped porous alumina array precursor, washed and dried in an oven at 80 °C for 6 hours, and then the mixture was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes.

[0026] Example 2 134.5 g of copper chloride and 68.2 g of zinc chloride were dissolved in 1 L of distilled water. The mixed solution and 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 °C and the pH of the solution in the continuous neutralization reactor was controlled to 5.0.

[0027] 37.5 g of aluminum nitrate nonahydrate was dissolved in 100 mL of distilled water and neutralized with ammonia water at room temperature, with an end point pH of 5.0. After neutralization, the aluminum paste was heated to 80 °C for 12 h in situ to evaporate the ammonia. Subsequently, the slurry after ammonia evaporation was sealed and heated to 180 °C for 24 h to obtain a nanorod-shaped porous alumina array precursor.

[0028] The copper-zinc slurry was mixed with the nanorod-shaped porous alumina array precursor, washed and dried in an oven at 80 °C for 6 hours, and then the mixture was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes.

[0029] Example 3 241.6 g of copper nitrate trihydrate and 148.7 g of zinc nitrate hexahydrate were dissolved in 1 L of distilled water. The mixed solution and 1 mol / L Na2CO3 aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 °C and the pH of the solution in the continuous neutralization reactor was controlled to 5.0.

[0030] 37.5 g of aluminum nitrate nonahydrate was dissolved in 100 mL of distilled water and neutralized with ammonia water at room temperature, with an end point pH of 9.0. After neutralization, the aluminum paste was heated to 80 °C for 12 h in situ to evaporate the ammonia. Subsequently, the slurry after ammonia evaporation was sealed and heated to 180 °C for 24 h to obtain a nanorod-shaped porous alumina array precursor.

[0031] The copper-zinc slurry was mixed with the nanorod-shaped porous alumina array precursor, washed and dried in an oven at 80 °C for 6 hours, and then the mixture was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes.

[0032] Example 4 241.6 g of copper nitrate trihydrate and 148.7 g of zinc nitrate hexahydrate were dissolved in 1 L of distilled water. The mixed solution and 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 90 ° C and the pH of the solution in the continuous neutralization reactor was controlled to 9.0.

[0033] 37.5 g of aluminum nitrate nonahydrate was dissolved in 100 mL of distilled water and neutralized with ammonia water at room temperature, with an end point pH of 5.0. After neutralization, the aluminum paste was heated to 80 °C for 12 h in situ to evaporate the ammonia. Subsequently, the slurry after ammonia evaporation was sealed and heated to 180 °C for 24 h to obtain a nanorod-shaped porous alumina array precursor.

[0034] The copper-zinc slurry was mixed with the nanorod-shaped porous alumina array precursor, washed and dried in an oven at 80 °C for 6 hours, and then the mixture was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes.

[0035] Example 5 241.6 g of copper nitrate trihydrate and 148.7 g of zinc nitrate hexahydrate were dissolved in 1 L of distilled water. The mixed solution and 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 ° C and the pH of the solution in the continuous neutralization reactor was controlled to 5.0.

[0036] 37.5 g of aluminum nitrate nonahydrate was dissolved in 100 mL of distilled water and neutralized with ammonia water at 60 °C, with an end point pH of 9.0. After neutralization, the aluminum paste was heated to 80 °C for 12 h in situ to evaporate the ammonia. Subsequently, the slurry after ammonia evaporation was sealed and heated to 180 °C for 24 h to obtain a nanorod-shaped porous alumina array precursor.

[0037] The copper-zinc slurry was mixed with the nanorod-shaped porous alumina array precursor, washed and dried in an oven at 80 °C for 6 hours, and then the mixture was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes.

[0038] Example 6 241.6 g of copper nitrate trihydrate and 148.7 g of zinc nitrate hexahydrate were dissolved in 1 L of distilled water. The mixed solution and 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 ° C and the pH of the solution in the continuous neutralization reactor was controlled to 5.0.

[0039] 37.5 g of aluminum nitrate nonahydrate was dissolved in 100 mL of distilled water and neutralized with ammonia water at room temperature, with an end point pH of 5.0. After neutralization, the aluminum paste was heated to 100 °C for 24 h in situ to evaporate the ammonia. Subsequently, the slurry after ammonia evaporation was sealed and heated to 180 °C for 24 h to obtain a nanorod-shaped porous alumina array precursor.

[0040] The copper-zinc slurry was mixed with the nanorod-shaped porous alumina array precursor, washed and dried in an oven at 80 °C for 6 hours, and then the mixture was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes.

[0041] Example 7 241.6 g of copper nitrate trihydrate and 148.7 g of zinc nitrate hexahydrate were dissolved in 1 L of distilled water. The mixed solution and 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 ° C and the pH of the solution in the continuous neutralization reactor was controlled to 5.0.

[0042] 37.5 g of aluminum nitrate nonahydrate was dissolved in 100 mL of distilled water and neutralized with ammonia water at room temperature, with an end point pH of 5.0. After neutralization, the aluminum paste was heated to 80 °C for 12 h in situ to evaporate the ammonia. Subsequently, the slurry after ammonia evaporation was sealed and heated to 220 °C for 48 h to obtain a nanorod-shaped porous alumina array precursor.

[0043] The copper-zinc slurry was mixed with the nanorod-shaped porous alumina array precursor, washed and dried in an oven at 80 °C for 6 hours, and then the mixture was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes.

[0044] Example 8 241.6 g of copper nitrate trihydrate and 148.7 g of zinc nitrate hexahydrate were dissolved in 1 L of distilled water. The mixed solution and 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 ° C and the pH of the solution in the continuous neutralization reactor was controlled to 5.0.

[0045] 375.1 g of aluminum nitrate nonahydrate was dissolved in 100 mL of distilled water and neutralized with ammonia water at room temperature, with an end point pH of 5.0. After neutralization, the aluminum paste was heated to 80 °C for 12 h in situ to evaporate the ammonia. Subsequently, the slurry after ammonia evaporation was sealed and heated to 180 °C for 24 h to obtain a nanorod-shaped porous alumina array precursor.

[0046] The copper-zinc slurry was mixed with the nanorod-shaped porous alumina array precursor, washed and dried in an oven at 80 °C for 6 hours, and then the mixture was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes.

[0047] Example 9 241.6 g of copper nitrate trihydrate and 148.7 g of zinc nitrate hexahydrate were dissolved in 1 L of distilled water. The mixed solution and 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 ° C and the pH of the solution in the continuous neutralization reactor was controlled to 5.0.

[0048] 37.5 g of aluminum nitrate nonahydrate was dissolved in 100 mL of distilled water and neutralized with ammonia water at room temperature, with an end point pH of 5.0. After neutralization, the aluminum paste was heated to 80 °C for 12 h in situ to evaporate the ammonia. Subsequently, the slurry after ammonia evaporation was sealed and heated to 180 °C for 24 h to obtain a nanorod-shaped porous alumina array precursor.

[0049] The copper-zinc slurry was mixed with the nanorod-shaped porous alumina array precursor, washed and dried in an oven at 120 °C for 12 hours, and then the mixture was calcined in a muffle furnace at 300 °C in air atmosphere for 30 minutes.

[0050] Example 10 241.6 g of copper nitrate trihydrate and 148.7 g of zinc nitrate hexahydrate were dissolved in 1 L of distilled water. The mixed solution and 1 mol / L NaOH aqueous solution were simultaneously added to the continuous neutralization reactor through a metering pump, the temperature was maintained at 30 ° C and the pH of the solution in the continuous neutralization reactor was controlled to 5.0.

[0051] 37.5 g of aluminum nitrate nonahydrate was dissolved in 100 mL of distilled water and neutralized with ammonia water at room temperature, with an end point pH of 5.0. After neutralization, the aluminum paste was heated to 80 °C for 12 h in situ to evaporate the ammonia. Subsequently, the slurry after ammonia evaporation was sealed and heated to 180 °C for 24 h to obtain a nanorod-shaped porous alumina array precursor.

[0052] The copper-zinc slurry was mixed evenly with the nanorod-shaped porous alumina array precursor, washed and dried in an oven at 80 °C for 6 hours, and then the mixture was calcined in a muffle furnace at 400 °C in air atmosphere for 60 minutes.

[0053] Comparative Example 241.6 g of copper nitrate trihydrate, 148.7 g of zinc nitrate hexahydrate and 37.5 g of aluminum nitrate nonahydrate were dissolved in 1 L of distilled water. The mixed solution and 1 mol / L of NaOH aqueous solution were simultaneously added to a continuous neutralization reactor through a metering pump, and the temperature was maintained at 30 °C and the pH of the solution in the continuous neutralization reactor was controlled to be 5.0. The mixture was washed and dried in an oven at 80 °C for 6 hours. The mixture was then calcined in a muffle furnace at 300 °C in an air atmosphere for 30 minutes.

[0054] Activity test conditions: The copper-zinc-supported methanol synthesis catalyst was used to prepare methanol from syngas, and the activity of the catalyst was evaluated in a micro-fixed bed continuous flow reactor. The catalyst loading was 4 mL, and the sample was heated in a H2 / N2 mixed gas containing 5% H2 at 20 °C h under normal pressure before the reaction.-1 The temperature was programmed to rise to 250°C for 10 h for reduction treatment. Subsequently, the catalyst was heated in a syngas atmosphere with the following composition: CO (13–15%), CO2 (3–5%), H2 (55–65%), and the remainder N2 at a space velocity of 10000 h -1 The methanol synthesis catalytic reaction was carried out under the conditions of 5.0 MPa, reaction pressure and reaction temperature of 250 °C, and the measured result was the initial activity. After the catalyst was heat treated for 5 hours under the conditions of synthesis gas atmosphere, normal pressure and 400 °C, it was restored to the above-mentioned activity evaluation conditions, and the measured activity result was the heat-resistant activity. The activity evaluation results of the embodiments and comparative examples are shown in Table 1: Table 1: Activity evaluation results

[0055] The activity evaluation results show that the catalyst prepared by the present invention has higher initial activity and post-heat-resistant activity than the comparative example, and the post-heat-resistant activity decay rate is also significantly lower than that of the comparative example. This result proves that the thermal stability of the catalyst can be effectively improved by forming a nanorod-shaped porous alumina array and confining copper-zinc nanoparticles.

[0056] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.

Claims

1. A method for preparing a methanol synthesis catalyst modified by an alumina array, characterized in that The nanorod-shaped porous alumina array is obtained by in-situ ammonia evaporation method, and the nanorod-shaped porous alumina carrier is used to confine the copper-zinc active particles and block the thermal migration path of the particles; the preparation method of the catalyst comprises the following steps: (1) neutralizing the copper salt and the zinc salt with an alkaline precipitant to obtain a copper-zinc slurry; (2) neutralizing the aluminum salt with ammonia water; (3) The aluminum slurry is heated to evaporate the ammonia; (4) The container is sealed, and the aluminum slurry is heated in situ and reacted again to obtain a nanorod-shaped porous alumina array precursor; (5) The nanorod-shaped porous alumina array precursor is mixed with copper-zinc slurry, and the mixture is washed, dried, and calcined to obtain an alumina array-modified methanol synthesis catalyst.

2. The method for preparing the methanol synthesis catalyst modified by aluminum oxide array according to claim 1, characterized in that The copper salt and zinc salt in step (1) are both soluble nitrates, sulfates and chlorides.

3. The method for preparing the methanol synthesis catalyst modified by aluminum oxide array according to claim 1, characterized in that The alkaline precipitant in step (1) is one of NaOH, NH3·H2O, NaHCO3 and Na2CO3.

4. The method for preparing the methanol synthesis catalyst modified by aluminum oxide array according to claim 1, characterized in that The precipitation pH in step (1) is 5–9 and the precipitation temperature is 30–90 °C.

5. The method for preparing the methanol synthesis catalyst modified by aluminum oxide array according to claim 1, characterized in that The precipitation pH in step (2) is 5–9 and the precipitation temperature is room temperature–60 °C.

6. The method for preparing the methanol synthesis catalyst modified by aluminum oxide array according to claim 1, characterized in that The ammonia evaporation temperature in step (3) is 80–100 °C and the ammonia evaporation time is 12–24 h.

7. The method for preparing the methanol synthesis catalyst modified by aluminum oxide array according to claim 1, characterized in that The temperature of the in-situ heating reaction in step (4) is 180-220 °C and the reaction time is 24-48 h.

8. The method for preparing the methanol synthesis catalyst modified by aluminum oxide array according to claim 1, characterized in that The molar ratio of copper, zinc and aluminum in step (5) is 10:5:1-10:5:

10.

9. The method for preparing the methanol synthesis catalyst modified by aluminum oxide array according to claim 1, characterized in that The drying process in step (5) is to dry at 80-120 °C for 6-12 hours.

10. The method for preparing the methanol synthesis catalyst modified by aluminum oxide array according to claim 1, characterized in that The calcination process in step (5) is to calcine in an air atmosphere at 300-400 °C for 30-60 minutes.